HARTA-HARTA YANG DIKENAKAN ZAKAT: SATU ANALISIS HUKUM - Buang, Ahmad Hidayat (Jurnal Syariah, 2019)
Zakat is collected from the income of certain properties. In general no income of properties other than those determined by the Syariah should be collected as zakat payment. However from time to time, the Islamic jurists have permitted the collection of income of properties not described by the law based on the principles of analogy and public interest. Although the use of the above principles has solved certain problems, many other properties which are considered, from the economic points of view, as "zakatable" are excluded. Following the thesis maintained by Professor al-Qaradhawi in his Fiqh al-Zakah, this article argues that the inclusion of income of properties as zakat payment should not be based on literal meaning of the text of the law, hut one has to formulate the general criteria contained in those texts so as to build a general rule which can be applied to all kinds of properties in respect of Zakat collection.